Ferroelasticity and piezoelectricity of organic–inorganic hybrid materials with a one-dimensional anionic structure: so similar, yet so different. Issue 15 (23rd March 2018) - Piecha-Bisiorek, Anna; Mencel, Klaudia; Kinzhybalo, Vasyl; Szota, Aleksandra; Jakubas, Ryszard; Medycki, Wojciech; Zawrocki, Wiktor
Abstract : The synthesis, structural aspects, and thermal and dielectric analysis for new members of the ferroic family, polynuclear Bi(iii ) and Sb(iii ) halide complexes based on a pyrazolium cation with the formulas (C3 N2 H5 )[BiCl4 ]·H2 O and (C3 N2 H5 )[SbCl4 ]·H2 O, are presented. Abstract : The synthesis, structural aspects, thermal and dielectric analysis for new members of the ferroic family, polynuclear Bi(iii ) and Sb(iii ) halide complexes based on a pyrazolium cation with the formulas (C3 N2 H5 )[BiCl4 ]·H2 O and (C3 N2 H5 )[SbCl4 ]·H2 O, are presented. The former compound was found to undergo a ferroic phase transition of the ferroelastic type at 213/219 K (cooling/heating scans), whereas, the latter one exhibited a piezoelectric feature in the dielectric response function. The molecular motions of pyrazolium cations were analyzed based on the spin–lattice relaxation time of 1 H NMR measurements.